PENGARUH GAYA BELAJAR SISWA DAN STRATEGI PEMBELAJARAN GURU TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN EKONOMI (LINTAS MINAT) DI SMA NEGERI 1 KALASAN - Maria Prabawati; FX. Muhadi (Jurnal Pendidikan Ekonomi dan Akuntansi, 2021)
This study aimed to determine whether there were: (1) a positive influence of students’ learning styles on learning achievements in economic subjects (cross interests) for high school students of Class XI MIPA, and (2) a positive influence of teachers’ learning strategies on learning achievements in economic subjects (cross- interest) high school students of class XI MIPA. This research was an ex-post facto research-correlation study conducted on April 8-19, 2021. The populations of this research were all students of Class XI MIPA SMA Negeri 1 Kalasan with a total of 144 students. The samples of this research were totaling 108 students, taken by using a simple random sampling technique. The data were collected by using questionnaires and documentation. The hypothesis was tested by using Spearman Rank correlation. The results of this study were: (1) there was a positive effect of students’ learning styles on learning achievements in economic subjects (cross interests) for high school students of Class XI MIPA, with an r value of 0,213 and a significance value of 0,013 level of significance 0,05; and (2) there was no positive effect of teachers’ learning strategies on learning achievements in economics subjects (cross interests) for high school students of Class XI MIPA, with an r-count value of 0,142 and a significance value of 0,071 level of significance 0,05.Keywords: Students’ learning achievement, students’ learning styles, teachers’ learning strategy.